Analyses of Daily Market Impact Using Execution and Order Book Information - Yamada, Kenta; Mizuno, Takayuki (Frontiers in Physics, 2020)
We analyzed the Tokyo Stock Exchange (TSE) for a 29-month period from August 2014 to December 2016, including every transaction and order book snapshot, and confirmed through a simple statistical test that the market impact depends on each stock. Based on a correlation analysis, we found that the market impact slowly changes over time. From an order book analysis, negative correlations were found between the market impact and the averaged limit order volumes in the order book. We also clarified that one of the factors of market impact is the volume of limit orders in the order book.